Soil enzyme stoichiometry is tightly linked to microbial community composition in successional ecosystems after glacier retreat. (November 2021) - Wang, Jipeng; Wu, Yanhong; Li, Jingji; He, Qingqing; Bing, Haijian
Abstract: Soil enzyme stoichiometry has been proposed to reflect microbial resource limitation. However, this view overlooks the profound variations in microbial community composition and soil abiotic properties that may also affect enzyme stoichiometry. In successional subalpine ecosystems after glacier retreat, we found that the stoichiometry of soil carbon-, nitrogen- and phosphorus-acquisition enzymes was strongly associated with the microbial community composition. Soil abiotic properties (pH and soil organic matter quality) may also affect enzyme stoichiometry directly, or indirectly through microbial community composition. In contrast, microbial resource status was weakly related to enzyme stoichiometry. Thus, precautions should be taken when using enzyme stoichiometry as an indicator of microbial resource limitation. The close relationship between microbial community composition and enzyme stoichiometry suggests that genetic potential is linked to the enzyme activity in subalpine soils. Highlights: Soil enzyme stoichiometry was tightly linked to microbial commuinty composition in a glacier retreat area. Enzyme stoichiometry was also associated with soil abiotic properties. In contrast, enzyme stoichiometry was weakly related to microbial resource status. Soil enzyme stoichiometry may not reliably reflect microbial resource limitation.